MENGUKUR KONTRIBUSI LANGGANAN E-JOURNAL SCIENCEDIRECT TERHADAP PRODUKTIVITAS PERGURUAN TINGGI MENGGUNAKAN STUDI BIBLIOMETRIK: STUDI KASUS UNIVERSITAS ANDALAS - Saputra, Andi (BACA: Jurnal Dokumentasi dan Informasi, 2018)
This study aims to measure the level of productivity of authors affiliated with Andalas University in journal published by ScienceDirect, to illustrate the level of contribution and utilization rate of e-journal subscriptions at Andalas University. Descriptive bibliometric method is used to measure the researcher's performance. Data is retrieved over the last 10 years. Data collection techniques from the ScienceDirect use advanced search facilities, typing the "universitas andalas" and "andalas university" keywords in the search field for the affiliation category specific to the Journal article type. Author productivity is measured using descriptive statistical methods presented based on geographic (faculty), time period (year), publisher, author and collaboration pattern, and field of science. The results of this study indicate that although in the last 10 years, numbers of Andalas University publications in ScienceDirect trend tends to increase but in terms of the number is still small, only an average of 10 articles a year. The authorship collaboration pattern reached 0,82 with the number of collaborations with outside authors reaching 78%. Distribution of users is also not evenly distributed. Only two faculties have the most benefits of ScienceDirect, Faculty of Engineering and FMIPA.